Drying, film formation and open time of aqueous polymer dispersions : an investigation of different aspects by rheometry and inverse-micro-raman-spectroscopy (IMRS) - Ludwig, Imke (KIT Scientific Publishing, 2008)
The application properties and the final coating properties of waterborne polymer dispersions are poor compared to the ones of polymer solutions with organic solvents. This is expressed by a short open time and by inhomogeneities and defects that are visible in the final dry coating.Aim of this work is an investigation and discussion of the different aspects that are responsible for the poor application and coating properties of aqueous latex dispersions by experiments and model calculations.